Peranan Pentadbir sebagai Pencetus Penghasilan Inovasi dalam Kalangan Guru Inovatif Pendidikan Islam - Wan Ali Akbar Wan Abdullah; Khadijah Abdul Razak; Mohd Isa Hamzah; Nursafra Mohd Zhaffar (USIM Press, 2024)
Vol. 4 No. 1 (2020)